Preparing for a Bsal invasion into North America has improved multi-sector readiness - Olson, Deanna H.; Grant, Evan H. Campbell; Bletz, Molly; Piovia-Scott, Jonah; Lesbarrères, David; Kerby, Jacob L.; Adams, Michael J.; Breitman, Maria Florencia; Christman, Michelle R.; Forzán, María J.; Gray, Matthew J.; Hill, Aubree J.; et al. (Frontiers in Amphibian and Reptile Science, 2024)
Western palearctic salamander susceptibility to the skin disease caused by the amphibian chytrid fungus Batrachochytrium salamandrivorans (Bsal) was recognized in 2014, eliciting concerns for a potential novel wave of amphibian declines following the B. dendrobatidis (Bd) chytridiomycosis global pandemic. Although Bsal had not been detected in North America, initial experimental trials supported the heightened susceptibility of caudate amphibians to Bsal chytridiomycosis, recognizing the critical threat this pathogen poses to the North American salamander biodiversity hotspot. Here, we take stock of 10 years of research, collaboration, engagement, and outreach by the North American Bsal Task Force. We summarize main knowledge and conservation actions to both forestall and respond to Bsal invasion into North America. We address the questions: what have we learned; what are current challenges; and are we ready for a more effective reaction to Bsal’s eventual detection? We expect that the many contributions to preemptive planning accrued over the past decade will pay dividends in amphibian conservation effectiveness and can inform future responses to other novel wildlife diseases and extreme threats.